Vesicle trafficking: pleasure and pain from SM genes. - Toonen, R.F.G.; Verhage, M. (Trends in Cell Biology, 2003)
Most cells contain a variety of transport vesicles traveling to different destinations. Although many specific transport routes exist, the underlying molecular principles appear to be rather similar and conserved in evolution. It has become evident that formation of protein complexes named SNARE complexes between vesicle and target membrane is a central aspect of the final fusion reaction in many, if not all, routes and that SNARE complexes in different routes and species form in a similar manner. It is also evident that a second gene family, the Sec1/Munc18 genes (SM genes), plays a prominent role in vesicle trafficking. But, in contrast to the consensus and clarity about SNARE proteins, recent data on SM proteins in different systems produce an uncomfortable heterogeneity of ideas about their exact role, their site of action and their relation to SNARE proteins. This review examines whether a universal principle for the molecular function of SM genes exists and whether the divergence in SM gene function can be related to the unique characteristics of different transport routes.